(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Placentas in GDM pregnancy are large, heavier and shows microscopic alterations in form of villous edema, immaturity and fibrinoid degeneration. Such abnormal modifications in placentas are accountable for fetal hypoxia and raised perinatal morbidity and mortality. Studying of placental structure and its effect on fetus development is essential for developing effective screening, prevention, and management methods. Objectives: Studying gross morphological and histopathological changes in placenta of mothers with Gestational Diabetes Mellitus (GDM) and comparing them with normal pregnancy. Methodology: Present cross-sectional comparative study of placenta was conducted in 50 GDM and 50 normal pregnancies at tertiary care center of Pune, Maharashtra during September 2020 to August 2022. Results: Among GDM pregnancy, mean gestational age was significantly lower, mean fasting blood sugar was significantly higher compared to normal pregnancy (p<0.05). There was significantly higher placental weight, fasting sugar among GDM pregnancy, relationship of increased syncytial knots, villous stromal fibrosis, fibrinoid necrosis and chorangiosis between both groups was statistically significant (p<0.05). Conclusion: Placenta among GDM pregnancy were heavier with raised syncytial knots, presence of villous stromal fibrosis, fibrinoid necrosis and chorangiosis compared to normal pregnancy. Hence, we conclude that studying the histomorphology of the placentas in GDM can help with screening and management of both mother and fetus.